Mekanisma Dan Analisis Skim Agihan Zakat Di Universiti Kebangsaan Malaysia (UKM) Mengikut Maqasid Syariah - Azman Ab. Rahman; Muhammad Azhad Al-Bohari; Siti Nurhafizan Panglima; Ahmad Muhasim; Abubacarr Barrow (Universiti Sains Islam Malaysia, 2025)
Indexed by Scopus/MyCite